2001
DOI: 10.1177/104063870101300608
|View full text |Cite
|
Sign up to set email alerts
|

Endometritis in Postparturient Cattle Associated with Bovine Herpesvirus-4 Infection: 15 Cases

Abstract: Abstract. Suppurative, ulcerative endometritis associated with bovine herpesvirus-4 (BHV-4) infection was identified in 15 postparturient dairy cows from 5 separate dairies. Characteristic eosinophilic to amphophilic intranuclear viral inclusion bodies were identified within degenerate endometrial lining epithelium and endothelial cells. Bovine herpesvirus-4 was confirmed as the etiology by a combination of fluorescent antibody assays, viral isolation, heminested PCR, ultrastructural examination of the uterus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 25 publications
(89 reference statements)
5
50
0
1
Order By: Relevance
“…3e). The association of BoHV-4 with other pathogens in cases of metritis has been consistently reported in the past (2,9,10,15,19), and bacterially induced metritis in cattle persistently infected with BoHV-4 could possibly be exacerbated or become chronic following the recruitment from the bloodstream to the site of inflammation of macrophages persistently infected with BoHV-4. Production of COX2 and PGE2 in murine deciduas is well known to increase rapidly in response to a number of cell activators and inflammatory signals such as lipopolysaccharide (16,17).…”
mentioning
confidence: 99%
“…3e). The association of BoHV-4 with other pathogens in cases of metritis has been consistently reported in the past (2,9,10,15,19), and bacterially induced metritis in cattle persistently infected with BoHV-4 could possibly be exacerbated or become chronic following the recruitment from the bloodstream to the site of inflammation of macrophages persistently infected with BoHV-4. Production of COX2 and PGE2 in murine deciduas is well known to increase rapidly in response to a number of cell activators and inflammatory signals such as lipopolysaccharide (16,17).…”
mentioning
confidence: 99%
“…Association between reproductive disorders and viral infections of cattle reported in Turkey by different studies [21,22]. Clinically postpartum metritis has also been associated with BHV-4 demonstrated with various studies in different countries such as USA, Spain, Serbia, Italy, and Turkey [15,16,[23][24][25]. In this study, detection of antibodies against BVDV and BHV-4 in unvaccinated animals demonstrates that these cattle had contracted with these viruses.…”
Section: Discussionmentioning
confidence: 72%
“…It has no close relationship to other herpes viruses of the family Bovidae [13]. BHV-4 is a risk factor for some clinical symptoms such as abortion, conjunctivitis, metritis, stillbirth, reproductive deficiencies, pustular vulvovaginitis, ocular discharge and respiratoric changes [14][15][16]. Like other herpes viruses animals infected with BHV-4 develop a latent infection as a lifelong, asymptomatic infection [14] and virus reactivation and reexcretion occurs in these animals following any applications like glucocorticoid treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides this conundrum, scientific curiosity has driven the search for an evolutionary explanation for this virus, because in the virus´s world, it is an unique example of lateral transfer of a gene that encodes the core 2 beta-1,6-N-acetylglucosaminyltransferase (B1,6GnT) protein, an enzyme that has implications for the host immune system evasion (Markine-Goriaynoff et al 2003a). Several studies have been have made to detect the BoHV-4 (Frazier et al 2001, 2002, MarkineGoriaynoff et al 2003bDeim et al 2007;Elhassan et al 2011;Peréz et al 2011) and varying prevalence rates ranging from 4 to 50% in Europe (Luini et al 1985(Luini et al , 1986Truman et al 1986;Wellemberg et al 1999;Essmail et al 1999; Monge et al 2006), 14 to 70% in Africa (Kaminjolo et al 1972;Rweyemamu et al 1973;Theodoridis 1978;Eyanga 1989;Rossiter et al 1989;Marchot et al 1991;Woldemeskel et al 2000;Elhassan et al 2011), 2 to 88% in the USA (Potgieter and Mare 1971;Phillips et al 1983Phillips et al , 1989Naeem et al 1989;Guo et al 1998;Kruger et al 1991), 8.9 to 23.3% in Asia (Kwang 1999;Asano et al 2002); 69% in the Middle-East (House et al 1990;Gur et al 2010) and 84.4% of animals in Serbia (Nikolin et al 2007) have been reported. In Brazil, studies about BoHV-4 are still scarce.…”
Section: Introductionmentioning
confidence: 99%